Clotting effect of two coca leaf varieties on albino rat blood samples - Díaz Soriano, Ana María (2007)
This investigation evaluates the clotting effect of extracts of two varieties of coca leaves: Erytrhoxylum coca var. Coca and novogranatense Erytrhoxylum var. Truxillense. The aim of the study was to determine the shortest time of clotting of the blood samples of the albin rats. 34 males and female rats were selected to have 3 ml. of blood of each one. The blood samples were distributed in three probes containing: 0,06 ml. of physiological serum (control group), 0,06 ml. extract of E. coca lam var. coca (coca group), and 0,06 ml. of extract E. novogranatense var. truxillense (truxillense group). The clotting time for the control group was of 1,42 (±0.31) min, coca group: 1,38 (±0.26) min, truxillense group 1,83 (±0.55) min. The Anova analysis of the results showed significant differences between groups (p<0.01). The coca group showed the shortest clotting time of all groups. The truxillense group showed an inhibiting clotting effect compared to control group.